Does illness perception associate with disease symptoms in Behcet's disease? - ALİBAZ ÖNER, FATMA; YAĞAR, FEDAYİ; MUMCU, GONCA; İNANÇ, GÜZİDE NEVSUN; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (SPRINGER-VERLAG ITALIA SRL, 2019)
This study aims to assess the relationship between illness perception and disease course and symptoms in Behcet disease (BD). One hundred ten consecutive BD patients (F/M 50/60, mean age 38.5 +/- 9.88years) and 57 patients with Psoriasis as a disease control group (F/M 28/29, mean age 48.12 +/- 15.52) are included in this cross-sectional study. Illness perception is evaluated using a revised version of the Illness Perception Questionnaire (IPQ-R). In IPQ-R, the identity score reflecting the number of symptoms is higher in BD patients with musculoskeletal involvement than the others (6.77 +/- 2.91 vs. 5.08 +/- 3.3, respectively, p=0.007). The consequences score for musculoskeletal involvement (19.52 +/- 7.03) and timeline (acute/chronic) score for eye involvement (26.67 +/- 4.32) are also higher compared to patients without them (16.37 +/- 5.82 and 22.09 +/- 8.68) (p=0.011 and p=0.038), reflecting negative beliefs about the illness. The score of psychological attribution is higher in patients with psoriasis than BD (p=0.039), whereas the other subgroup scores are lower in patients with psoriasis compared to those of BD (p<0.05). This study provides a patient's perspective in the disease management process of BD using the IPQ-R questionnaire. A patient's own personal beliefs and emotional responses to their symptoms might affect the outcome measures, especially with musculoskeletal symptoms and eye involvement in BD. However, psychological attribution is found to be a prominent issue in psoriasis.
Keywords: Behcet's disease; Psoriasis; Illness perception; Disease management; QUALITY-OF-LIFE; SYSTEMIC-LUPUS-ERYTHEMATOSUS; IPQ-R; PSORIASIS; QUESTIONNAIRE; FATIGUE; STRESS; HEALTH; WORK